Synthesis and Physiochemical Properties of Zinc Layered Hydroxide-Cinnamate - Adam, Nurain; Ahmad Izaddin Sheikh Mohd Ghazali, Sheikh; Nadia Dzulkifli, Nur; Ain Jamion, Nurul; Jiwal, Khatyjah (International Journal of Engineering and Technology, 2018)
The intercalations of cinnamic acid into zinc layered hydroxide were synthesized by using simple direct method due to the less usage used and simple preparation steps. The physiochemical studies were done to determine the ability of zinc layered hydroxide to traps cinnamic acid in between its interlayer region. The FTIR shows new generation of peak such as OH group, C=O, C=C, C-O and trans C=C at 3379 cm-1, 1643 cm-1, 1578cm-1,1253 cm-1 and 873 cm-1, and increases in basal spacing at 22.06Çº indicate the intercalations of cinnamic acid into the zinc layered hydroxide were presence. The morphological surfaces show new changes toward the surfaces of the intercalated compounds.Â